2020
DOI: 10.1016/j.kint.2020.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Changes in kidney function follow living donor nephrectomy

Abstract: Better understanding of kidney function after living donor nephrectomy and how it differs by donor characteristics can inform patient selection, counselling, and follow-up care. To evaluate this, we conducted a retrospective matched cohort study of living kidney donors in Alberta, Canada between 2002-2016, using linked healthcare administrative databases. We matched 604 donors to 2,414 healthy non-donors from the general population based on age, sex, year of cohort entry, urban residence and the estimated glom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 58 publications
5
36
0
Order By: Relevance
“…The GFR decline in controls in the studies by Kasiske et al 4 and Lam et al 5 is similar to findings in previous reports in healthy populations. The GFR decline in donors is also consistent with previous reports.…”
Section: Disclosuresupporting
confidence: 91%
See 3 more Smart Citations
“…The GFR decline in controls in the studies by Kasiske et al 4 and Lam et al 5 is similar to findings in previous reports in healthy populations. The GFR decline in donors is also consistent with previous reports.…”
Section: Disclosuresupporting
confidence: 91%
“…The studies of Kasiske et al 4 and Lam et al 5 improve our understanding of GFR trends during the first 10 years following living kidney donation. The major strength of both studies is the comparison to an appropriate control group.…”
Section: Disclosurementioning
confidence: 97%
See 2 more Smart Citations
“…In our study, we found a significant decrease in GFR at 6 months of follow-up, which suggests that renal donors are approximately in stage 2 of CKD (50). Although it has been previously reported that living kidney donors experience an early reduction in GFR of 25-40% after nephrectomy, this decrease could improve in the long term (51). The fundamental principle is close to medical surveillance and the commitment of the donor and his family to maintain a healthy lifestyle, at 6 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%